Penentuan Arah Kiblat dengan Posisi Matahari di Pusat Ibu Kota Kabupaten Lampung - Jamil, A; Sakirman, Sakirman; Ardliansyah, Moelki Fahmi (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
Facing the Qibla is one part of the requirements for prayer that must be sought. But in fact, there are still many mosques and places of worship for Muslims that do not face the Qibla. This paper examines the method of determining the direction of the center of the district capital city in Lampung by utilizing the shadows of the sun reflected by an object. The use of sunlight in determining the Qibla direction with this model is known as raṣd al-qiblah. The center of the capital city of Lampung district which is used as a sample for determining the direction of the Qibla is expected to all districts have the same calculation results can refer to the center of the district capital. So that the schedule for the implementation of raṣd al-qiblah in the district capital center in Lampung can be used by the districts within it. This type of research is a field research using a descriptive- analytical model that describes the determination of the Qibla direction with the position of the sun as the main benchmark. The use of tools in determining the Qibla direction is also used as a verification medium. Raṣd al-qiblah time is the transit time of the sun over the Ka’bah which is generally applicable to the coordinates of the district capitals in all sub-districts provided that the raṣd al-qiblah time interval is not outside the Qiblah azimuth path or not more than the tolerance threshold value. The results of a study of the three district capital centers in Lampung show that the timing of the implementation of raṣd al-qiblah for the districts that cover the three district capital centers has a time difference, although not significant.